J Clin Res Med 2022
DOI: 10.31038/jcrm.2022555
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte, Lipid Metabolism in Alzheimer’s Disease and Glioblastoma

Abstract: The brain is a central key organ of the body containing the second highest lipid content only after adipose tissue. Lipids as the main structural components of biological membranes play important roles in a vast number of biological processes within the brain such as energy homeostasis, material transport, signal transduction, neurogenesis and synaptogenesis, providing a balanced cellular environment required for proper functioning of brain cells. Lipids and their metabolism are of great physiological importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 305 publications
(361 reference statements)
0
1
0
Order By: Relevance
“…Concerning the potential utilization of ACSBG1 blood levels as a biomarker, ACSBG1 is prominently concentrated in the brain, primarily within astrocytes 50 . In vitro studies have demonstrated that ACSBG1 knockdown leads to reduced lipid oxidation, closely associated with AD 51,52 It is important to note that further research with larger sample sizes is required to confirm and expand upon our findings.…”
Section: Discussionmentioning
confidence: 55%
“…Concerning the potential utilization of ACSBG1 blood levels as a biomarker, ACSBG1 is prominently concentrated in the brain, primarily within astrocytes 50 . In vitro studies have demonstrated that ACSBG1 knockdown leads to reduced lipid oxidation, closely associated with AD 51,52 It is important to note that further research with larger sample sizes is required to confirm and expand upon our findings.…”
Section: Discussionmentioning
confidence: 55%